ALOKASI DANA CSR SEBAGAI VARIABEL MODERASI ANTARA PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PERBANKAN - Basir S (Politeknik Negeri Batam, 2019)
Corporate value is influenced by many factors, one of which is through Good Corporate Governance. Corporate governance is a system that regulates and controls companies that are expected to provide and increase the value of the company to shareholders. The allocation of Corporate Social Responsibility funds is selected as a moderating variable because Corporate Social Responsibility activities are part of good corporate governance that is expected to strengthen Good Corporate Governance relationship with company value. The population in this study is the banking subsector companies listed on the BEI. Sampling technique using purposive sampling and based on predetermined criteria then the number of 22 samples of companies subsector banking. This research followed by the analysis by using Regression Moderation analysis. The result of the research shows that the implementation of Good Corporate Governance proxied with the Proportion of Independent Commissioners , Audit Committee , Independence Audit Committee , Frequency of Audit Committee Meeting and Frequency of Meeting of Board of Commissioner simultaneously have significant effect to company Value with CSR as moderation.